Development of magnetic nanocomposite hydrogels for removal of pesticide from water - Tanaka, Fabrício C. [UNESP]; Gonçalves, Daniel A.; Cena, Cícero R.; de Moura, Marcia R. [UNESP]; Aouada, Fauze A. [UNESP] (Elsevier, 2024)
Using magnetic and biodegradable polymers for removal of soluble pesticides can reduce environmental and human health damage caused by their presence in rivers, streams, and lakes. In this study, we develop and characterize the crystallinity and thermal properties of novel magnetic hydrogels based on polysaccharides, zeolites, and magnetite (Fe3O4) magnetic nanoparticles (MNs) functionalized with 3-aminopropyltriethoxysilane (Fe3O4@NH2), supported in poly(methacrylic acid)-co-polyacrylamide networks. The potential of the hydrogel for herbicide removal, specifically paraquat, is also investigated. The Fourier-transform infrared spectroscopy, X-ray diffraction analysis, thermogravimetric, kinetic, and swelling degree analysis results demonstrate that MNs do not affect the physicochemical properties and pesticide sorption. However, minor changes, such as the peak at 2θ = 35.57º representing the (311) plane of Fe3O4, confirmed the incorporation of MNs into the polymer matrix. The increase in pH caused an increase in the swelling degree from 1.2 to 10.0 w.w−1, indicating an increase both the pore size, and possibly, in the removal properties. The adsorption results of paraquat through ultraviolet–visible spectroscopy measurements show a small difference in absorptive capacity (qeq) between pure hydrogel (12.95 mg.g−1) and hydrogel with 2.0 % functionalized Fe3O4 NPs (12.99 mg.g−1). Overall, incorporating Fe3O4 NPs in the hydrogel matrix yields materials with promising characteristics and while offering easier, safer removal from the environment.
Keywords: Herbicide; Hydrogels; Magnetite; Nanocomposites; Thermal analyses